Access management in intermodal freight transportation: An explorative study of information attributes, actors, resources and activities. (June 2017) - Jacobsson, Stefan; Arnäs, Per Olof; Stefansson, Gunnar
Abstract: The purpose of this study is to identify the existing and required information attributes (i.e. the actual transmitted information) that need to be exchanged between the studied hubs and hauliers to improve their access management. Access management is the management of the process of actors accessing resources for specific activities in transportation systems. A literature review on the topic is followed by semi-structured interviews and focus group meetings with key stakeholders. This results in a classification framework that categorises the information attributes into sources (actors, resources and activities) and categories (static, historical, or dynamic). The study reveals deficiencies in the information exchange between the involved actors. The main finding of this work is a comprehensive compilation of identified information attributes presented in an analytical framework. The most important required information attributes are Actual pick-up time, Hub's loading point, Hub's unloading point, Occupancy rate, and Queuing status . This study contributes to new knowledge in the disciplines Management of Freight Transport Systems, Intermodal Transport Systems and Information Systems (IS). For future research, the identified framework must be tested in real-life scenarios to measure its performance and efficiency on access management.